Penetrating the Virus Monitoring and Analysis System Using Delayed Trigger Technique - Abdollah, M. F. (2010)
Virus Monitoring and Analysis System (VMAS) is generally used for monitoring and capturing virus behavior, and it can produce a report analysis which can be used by expert user to learn virus activity. There are several tools which have this capability, such as: Joebox, ThreatExpert, CWSandbox, and Sysinternals. Turns out, these tools are not fully perfect in analyzing the virus behavior. Therefore in this paper, we propose a technique to defeat such tools, by exploiting the limitation of VMAS in term of time monitoring, by introducing a new virus exploiting technique called Delayed Trigger Technique (DTT).